Floristic checklist and distribution of Trollius species (Ranunculaceae) in Kazakhstan - DINA KARABALAYEVA; MERUYERT KURMANBAYEVA; ADIL KUSMANGAZINOV; BEKTEMIR OSMONALI; MOLDIR ZHUMAGUL (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Karabalayeva D, Kurmanbayeva M, Kusmangazinov A, Osmonali B, Zhumagul M. 2025. Floristic checklist and distribution of Trollius species (Ranunculaceae) in Kazakhstan. Biodiversitas 26: 4103-4123. The genus Trollius, belonging to the family Ranunculaceae and order Ranunculales, includes species known for their ornamental and medicinal value. However, the current state of Trollius species in Kazakhstan remains insufficiently studied. This study provides a comprehensive floristic update on five species: T. altaicus, T. asiaticus, T. dschungaricus, T. lilacinus, and T. komarovii, the latter formerly assigned to Hegemone and recently transferred to Trollius. We analyzed a total of 391 herbarium specimens (including 8 newly collected specimens in 2023): T. altaicus (177), T. dschungaricus (129), T. lilacinus (75), T. asiaticus (7), and T. komarovii (3), from field studies and 12 domestic and international herbarium collections. Additionally, we utilized online biodiversity databases such as GBIF and iNaturalist. During recent fieldwork, four new localities were confirmed for T. altaicus and T. dschungaricus, with precise georeferencing, notably in the Western Altai (Ivanov Ridge), Zailiyskiy Alatau (Talgar District), Zailiyskiy-Kungei Alatau (Maloe Almatinskoe Gorge), and the Ketpen Ridge (Uygur and Raiymbek Districts). Using QGIS 3.28 and Google Earth, we produced updated distribution maps based on materials dated from 1826 to 2024. The confirmed range of Trollius species includes Southern, Southeastern, and Eastern Kazakhstan, covering the Altai, Saur, Tarbagatai, Dzungarian Alatau, the northern and western Tian Shan, and Kyrgyz Alatau regions. This study refines the known distribution of Trollius in Kazakhstan and fills important floristic gaps, particularly in high-mountain and border areas. Our results highlight the need for further monitoring and conservation of these species, especially those with restricted distribution such as T. komarovii. This updated dataset lays the groundwork for future taxonomic, ecological, and conservation research on Central Asian flora.